SOCIAL CHARACTERISTICS OF THE VICTIMS KILLED IN THE PLOVDIV DISTRICT OF THE REPUBLIC OF BULGARIA IN THE PERIOD 2008 – 2017 - Marin Baltov; Iliya Bivolarski; Vanina Mihaylova; Stela Yancheva (Science & Research, 2019)

(untitled)
Homicide is one of the ways to take someone’s life and to cause fear and uncertainty in society, but it has not been sufficiently studied. Materials and methodology: The victims of 113 homicides committed in the Plovdiv District during the period 2008 – 2017 were studied. Their autopsies were carried out at the Forensic Medicine Department at Sveti Georgi University Multiprofile Hospital for Active Treatment – City of Plovdiv. The obtained results are processed statistically and are presented graphically. It was found that the victims of homicide accounted for 2.72% of the autopsies performed in the Department for the same period. The dynamics of the homicides over the years show a pronounced downward trend. Victims of homicides were 75 men (66.37% ± 8.71%) and 38 women (33.63% ± 6.20%). Urban residents are 60 of the victims (53.09% ± 4.69%), while the residents of villages are 51 (45.13% ± 4.68%). Two of the victims are foreigners. There are 6 children and one adolescent among the victims and the rest are evenly distributed in the different age groups. The most common mean of homicide is a hard blunt object (42.48% ± 3.99%), and the most commonly used tools are sharp objects and firearms (24.78% ± 4.06%). In 13 cases, other methods were used.